Increased number of glucocorticoid receptor-β–expressing cells in the airways in fatal asthma - Christodoulopoulos, Pota; Leung, Donald Y.M.; Elliott, Mark W.; Hogg, James C.; Muro, Shigeo; Toda, Masao; Laberge, Sophie; Hamid, Qutayba A. (Journal of allergy and clinical immunology, 2000)
Background: We have recently demonstrated an increased number of glucocorticoid receptor-β (GRβ)–positive cells in steroid-insensitive subjects with severe asthma. Insensitivity to steroids may be a major contributing factor in fatal asthma; however, no such direct evidence has been report previously. Objective: Our aims were to investigate the expression of GRβ immunoreactivity, an endogenous inhibitor of steroid action previously associated with steroid insensitivity, within the airways of patients who died of slow-onset fatal asthma and to compare its expression in patients with emphysema and in nonasthmatic subjects who died of unrelated causes. Sections from airways, both large and small, were obtained from 7 patients who died of asthma, 6 who died from emphysema, and 8 who died from nonpulmonary diseases. Sections from lungs of 6 patients with mild asthma whose lungs were resected for carcinoma were also included as controls. Methods: Tissue samples were processed for immunocytochemistry with a polyclonal antibody to GRβ with use of the avidin-biotin technique and with monoclonal CD3, major basic protein, CD68, and elastase antibodies with the alkaline phosphatase–anti-alkaline phosphatase technique. Sequential immunocytochemistry was performed to phenotype the GRβ immunoreactive cells. Tissue sections from both large (>2 mm) and small (<2 mm) airways were examined. Results: There was a significantly greater number of GRβ immunoreactive cells in fatal asthma compared with emphysema and controls (P < .001 and P < .05, respectively). There was no difference in the expression of GRβ in emphysema compared with controls. GRβ immunoreactivity was also significantly higher in fatal asthma compared with mild asthma. The expression of GRβ in the small airways of patients with severe asthma did not differ significantly from that in the large airways. The majority of GRβ-positive cells were T cells and to a lesser extent eosinophils, macrophages, and neutrophils. Conclusion: The results of this study support the association of GRβ expression with fatal asthma and suggest that alternative anti-inflammatory agents need to be considered in the acute setting for patients who are not responding to steroid therapy. (J Allergy Clin Immunol 2000;106:479-84.)